Supervisi Optimalisasi Kesiapan Mahasiswa Pendidikan Fisika untuk Program Kampus Mengajar: Analisis Wawancara Mendalam - Irvani, Asep Irvan; Diniya, Diniya; Kaniawati, Ida; Sudarsyah, Asep (Jurnal Pendidikan Fisika dan Sains (JPFS), 2024)
Kampus Mengajar Program is part of the Merdeka Belajar Kampus Merdeka (MBKM) initiative aimed at improving literacy and numeracy skills among students in underprivileged schools. This study explores strategies for optimizing supervision and preparing physics education students for participation in the program. Using a qualitative approach, in-depth interviews were conducted with lecturers from a physics education study program at a private university. The findings revealed that lecturers have a strong understanding of the program's objectives, yet the primary focus on elementary and middle school levels poses challenges in integrating physics-specific expertise. Students require comprehensive preparation, including pedagogical skills, mental readiness, and technological proficiency. Product-based assignments, such as teaching modules and learning media, along with process-based evaluations, were deemed effective in bridging field experiences with graduate learning outcomes (CPL). The synergy between supervision and the Kampus Mengajar Program fosters holistic learning, enhancing students’ practical skills. Curriculum adjustments to better integrate physics into elementary education contexts are necessary to address the gap in subject relevance. With structured supervision strategies and adequate preparation, the Kampus Mengajar Program can enhance students’ readiness as competent and adaptable educators in a dynamic educational landscape.